2002
DOI: 10.1021/jp020140q
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Yb3+ Aquo Ion and Chloro Complexes in Aqueous Solutions at Up to 500 °C and 270 MPa

Abstract: We report here on X-ray absorption fine structure (XAFS) measurements used to determine the structure of the Yb 3+ ion in aqueous solutions over a range of temperatures from 25 to 500 °C and pressures up to 270 MPa. Fluorescence Yb L 3 -edge spectra were collected separately from nitrate (0.006m Yb/0.16m HNO 3 ) and chloride (0.006 m YbCl 3 /0.017 m HCl) aqueous solutions within a hydrothermal diamond anvil cell. The Yb-O distance of the Yb 3+ aquo ion in the nitrate solution exhibits a uniform reduction at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Fig. 10a shows that in situ XAS studies of RCl 3 solutions (R = La 3+ , Nd 3+ , Gd 3+ , Yb 3+ ) as a function of temperature (25-500°C, P to 2.6 kbar) confirm these trends for chloride complexes (Mayanovic et al, 2002a(Mayanovic et al, , 2002b(Mayanovic et al, , 2007(Mayanovic et al, , 2009a. These in situ spectroscopic studies also demonstrate a general decrease in coordination number with increasing temperature, from~8 to 9 at 25°C (note the relatively large errors compared to Persson et al (2008), which reflects the use of the hydrothermal diamond anvil cell at higher temperature) to 6 to 7 at 500°C (Fig.…”
Section: Speciesmentioning
confidence: 60%
See 3 more Smart Citations
“…Fig. 10a shows that in situ XAS studies of RCl 3 solutions (R = La 3+ , Nd 3+ , Gd 3+ , Yb 3+ ) as a function of temperature (25-500°C, P to 2.6 kbar) confirm these trends for chloride complexes (Mayanovic et al, 2002a(Mayanovic et al, , 2002b(Mayanovic et al, , 2007(Mayanovic et al, , 2009a. These in situ spectroscopic studies also demonstrate a general decrease in coordination number with increasing temperature, from~8 to 9 at 25°C (note the relatively large errors compared to Persson et al (2008), which reflects the use of the hydrothermal diamond anvil cell at higher temperature) to 6 to 7 at 500°C (Fig.…”
Section: Speciesmentioning
confidence: 60%
“…Since 1998, a number of studies have investigated the behavior of simple hydrated REE ions (Mayanovic et al, 2002a(Mayanovic et al, , 2002b(Mayanovic et al, , 2007(Mayanovic et al, , 2009a(Mayanovic et al, , 2009bRagnarsdottir et al, 1998). These studies, however, have focused on the hydration structure and co-ordination of these ions, and have not attempted to revise the values recommended by Shock (1997) and Shock and Helgeson (1988).…”
Section: Thermodynamic Stability Of Simple Hydrated Ionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study on dilute (*10 -2 M) ytterbium (III) chloride solutions by Mayanovic et al showed that under high pressure and temperature (500°C and 270 MPa), YbCl 2 ? Á(H 2 O) 5 is the predominant species [22]. Using X-ray absorption fine structure spectroscopy (XAFS), they determined that all five water molecules were directly coordinated to the Yb metal center.…”
Section: Introductionmentioning
confidence: 99%